Pengabdian Kepada Masyarakat Akademi Maritim Nasional Jakarta Raya (Aman Jaya) dalam Upaya Pencegahan Judi Online di Majelis Taklim Nurul Irfan, Koja, Jakarta Utara - Agung Kwartama; Lie Adek; Sumiyatiningsih Sumiyatiningsih; Didik Indriawan (Universitas 45 Surabaya, 2024)
The use of this technology has driven rapid business growth, because various information has been presented sophisticatedly and easily obtained, and through long-distance relationships utilizing telecommunications technology can be used as material for carrying out further business steps. The parties involved in the transaction do not need to meet in person, simply through computer and telecommunications equipment, such conditions are a sign of the beginning of the cyber era. Gambling or gambling in article 1 of Law Number 7 of 1974 concerning the Control of Gambling is referred to as a criminal act of gambling and is identical to crime, but the definition of a criminal act of gambling is basically not stated clearly and in detail either in the Criminal Code or in Law Number 7 of 1974 concerning the Control of Gambling.